2015
DOI: 10.1021/acs.jpca.5b03222
|View full text |Cite
|
Sign up to set email alerts
|

Release of Oxygen from Palladium Oxide Cluster Ions by Heat

Abstract: Palladium oxide cluster ions, PdnOm(+), were prepared in the gas phase using laser ablation of a palladium rod in the presence of oxygen. The cluster ions were heated to 1000 K downstream from the cluster source (post heating), and the abundance of PdnOm(+) (n = 2-7) was examined using mass spectrometry. Temperature-programmed desorption experiments revealed that an oxygen molecule is released from oxygen-rich PdnOm(+), forming oxygen-deficient PdnOm-2(+). It was found that Pd6O4(+) was thermally stable up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(91 reference statements)
5
8
0
Order By: Relevance
“…The CID processes observed in the present experiment were also consistent to some extent with the results of the mass spectrometric study on thermal dissociation of Pd n O m + . 12 In the following sections of this study, the CCSs and structures will be discussed for Pd , respectively, which were confirmed by the 2D plot (Figure 2). These overlap contributions are not used in the discussion below.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…The CID processes observed in the present experiment were also consistent to some extent with the results of the mass spectrometric study on thermal dissociation of Pd n O m + . 12 In the following sections of this study, the CCSs and structures will be discussed for Pd , respectively, which were confirmed by the 2D plot (Figure 2). These overlap contributions are not used in the discussion below.…”
Section: Methodssupporting
confidence: 66%
“…This argument was obtained from the results of the mass spectra at the higher injection energies (Figure 1b,c), and it was also supported by the results reported in the previous study. 12 Plots of the experimental and theoretical CCSs of Pd , the CCS of the most stable 2D branched structure, Ω calc = 60.5 Å 2 , along with those of the two 3D compact structures with low relative energies, Ω calc = 59.6 and 58.6 Å 2 , was found to be in good agreement with the experimental CCS (Ω exp = 59.1 ± 1.4 Å 2 ). Thus, the 2D branched isomer and 3D compact structures containing a tetrahedral metal-core configuration were assigned as plausible structures.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…The Pt 3 O 4 + -catalyzed decomposition of NO was investigated by TDS and MS. Details of the experimental setup are shown in Figure S3. The gas-phase Pt clusters were formed in a cluster source: a Pt metal rod (Furuya Metal Co., Ltd.) was vaporized by a Nd:YAG pulsed laser (355 nm) in the presence of 0.5% oxygen diluted with helium (total stagnation pressure = 0.8 MPa). The generated Pt n O m + ( n = 1–4) reacted with NO molecules in the fast flow reactor where He-diluted NO gas was introduced through a gas valve.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…As for the previous cluster research to understand the oxygen–palladium interactions, studies were limited mainly on Pd n O m + cluster cations. Experimentally, Miyajima and Mafuné identified the compositions of Pd n O m + up to n = 7 by thermal desorption. According to this report, a variety of oxides including oxygen-deficient and oxygen-rich compositions were identified.…”
Section: Introductionmentioning
confidence: 99%